2020
DOI: 10.1142/s012906572050029x
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia Diagnosis by EEG Temporal and Spectral Descriptors: An Anomaly Detection Approach

Abstract: Diagnosis of learning difficulties is a challenging goal. There are huge number of factors involved in the evaluation procedure that present high variance among the population with the same difficulty. Diagnosis is usually performed by scoring subjects according to results obtained in different neuropsychological (performance-based) tests specifically designed to this end. One of the most frequent disorders is developmental dyslexia (DD), a specific difficulty in the acquisition of reading skills not related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 90 publications
0
23
0
1
Order By: Relevance
“…The ability to use high temporal (EEG) and spatial (fMRI) resolution during experimental paradigms make these techniques excellent tools for the identification of physiological correlates of reading processes (Carter et al, 2019;Duffy et al, 1980). It has been demonstrated that these tools can be useful in the evaluation of reading impairments (Gallego-Molina et al, 2022;Ortiz et al, 2020). Importantly, these studies have demonstrated that assessment of reading processes using neuro-imaging tools can lower the age of diagnosis for children with dyslexia (Chyl et al, 2021;Ortiz et al, 2020) and identify abnormal neural activation patterns prior to formal literacy instruction (Schiavone et al, 2014;Wilkinson et al, 2020).…”
Section: Neuroscience Of Reading Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to use high temporal (EEG) and spatial (fMRI) resolution during experimental paradigms make these techniques excellent tools for the identification of physiological correlates of reading processes (Carter et al, 2019;Duffy et al, 1980). It has been demonstrated that these tools can be useful in the evaluation of reading impairments (Gallego-Molina et al, 2022;Ortiz et al, 2020). Importantly, these studies have demonstrated that assessment of reading processes using neuro-imaging tools can lower the age of diagnosis for children with dyslexia (Chyl et al, 2021;Ortiz et al, 2020) and identify abnormal neural activation patterns prior to formal literacy instruction (Schiavone et al, 2014;Wilkinson et al, 2020).…”
Section: Neuroscience Of Reading Researchmentioning
confidence: 99%
“…It has been demonstrated that these tools can be useful in the evaluation of reading impairments (Gallego-Molina et al, 2022;Ortiz et al, 2020). Importantly, these studies have demonstrated that assessment of reading processes using neuro-imaging tools can lower the age of diagnosis for children with dyslexia (Chyl et al, 2021;Ortiz et al, 2020) and identify abnormal neural activation patterns prior to formal literacy instruction (Schiavone et al, 2014;Wilkinson et al, 2020). The purported reduction in the age of diagnosis using physiological markers introduces the possibility of a foundational improvement in the effectiveness of reading intervention outcomes.…”
Section: Neuroscience Of Reading Researchmentioning
confidence: 99%
“…The EEG data used in this work was provided by the Leeduca Study Group at the University of Málaga [6]. EEG signals were recorded using the Brainvision acticHamp Plus with 32 active electrodes (actiCAP, Brain Products GmbH, Germany) at a sampling rate of 500 Hz during 15 minutes sessions, while presenting an auditory stimulus to the subject.…”
Section: Database and Stimulusmentioning
confidence: 99%

Temporal EigenPAC for dyslexia diagnosis

Gallego-Molina,
Formoso,
Ortiz
et al. 2021
Preprint
Self Cite
“…EEG data used in this work was provided by the Leeduca Reserch Group at the University of Málaga [10]. EEG signals were recorded using the Brainvision acticHamp Plus with 32 active electrodes (actiCAP, Brain Products GmbH, Germany) at a sampling rate of 500 Hz during 15 minute sessions, while presenting an auditory stimulus to the subject.…”
Section: Database and Stimulusmentioning
confidence: 99%